Effects of FABP2 Ala54Thr gene polymorphism on obesity and metabolic syndrome in middle-aged Korean women with abdominal obesity - Han, Tae-Kyung; So, Wi-Young (Central European Journal of Public Health, 2019)
OBJECTIVES: Asians (including Chinese, Japanese and Koreans), who generally have a relatively smaller body size and a lower mean body mass index (BMI), have a relatively higher risk of developing android-type obesity than westerners. Substitution of alanine for threonine (Ala54Thr) on the FABP2 gene (rs 1799883) is related to insulin resistance and obesity. However, few studies have examined this substitution in Koreans, and the number of Korean subjects in those studies is limited. For this reason, we investigated the differences between the FABP2 Ala54Thr polymorphism and obesity, hemodynamic variables, blood lipid profile results, and insulin resistance among middle-aged Korean women with abdominal obesity. METHODS: We studied 243 middle-aged community-dwelling Korean women with abdominal obesity from Gyeonggi Province, Republic of Korea, who had no history of taking chronic medications. We examined each subject (n = 243) for the presence of FABP2 Ala54Thr polymorphism using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Subjects were also examined for obesity hemodynamic variables (n = 243), lipid profiles (n = 142), and insulin resistance (n = 142). RESULTS: Of the 243 subjects, 117 had AA ("normal") homozygotic genotype, 100 had AT heterozygotic genotype, and 26 had TT homozygotic genotype for the FABP2 Ala54Thr polymorphism. The AT heterozygotic individuals had a significantly higher mean waist-to-hip ratio, abdominal fat area, and visceral fat area than individuals with other genotypes. TT homozygotic individuals had higher mean triglyceride and fasting glucose levels than individuals with other genotypes. CONCLUSIONS: The results of this study show that the FABP2 Ala54Thr polymorphism was associated with central obesity and obesity-related metabolic syndrome among middle-aged Korean women.
Keywords: Fatty Acid-Binding Proteins; proteiny vázající mastné kyseliny; Humans; lidé středního věku; polymorfismus genetický; Korejská republika; analýza polymorfismu délky amplifikovaných restrikčních fragmentů; Female; Genotype; lidé; Waist-Hip Ratio; abdominální obezita; Polymorphism, Genetic; Republic of Korea; metabolický syndrom; Amplified Fragment Length Polymorphism Analysis; Obesity, Abdominal; ženské pohlaví; Middle Aged; Metabolic Syndrome; polymerázová řetězová reakce; Polymerase Chain Reaction; poměr pasu a boků; genotyp